Pareceristas - admin, admin (Outros Tempos: Pesquisa em Foco - História, 2012)
Dr. Alan Kardec Gomes Pachêco Filho (UEMA) Dr.Alexandre F. Corrêa (UFMA) Ms. Antonio Evaldo A. Barros (UFMA) Dra. Cláudia Cristina A. Atallah (USS-RJ) Dr. Cláudio Zanonni (UFMA) Dr. Fernando Atique (USP) Dr. George Félix Cabral de Souza (UFPE) Dra. Gisele Sanglard (USS-RJ) Dra. Grete Soares Pfluger (UEMA) Dra. Guida Marques (Universidade Nova de Lisboa (FCSH) e EHESS Dra. Helidacy Maria Muniz Corrêa (UEMA) Dr. Henrique de Paula Borralho (UEMA) Dra. Júlia Constança P. Camêlo (UEMA) Dra. Maria Mirtes dos Santos Barros (UFAMA) Dr. Ricieri Carlini Zarzol (UFMA) Dra. Tatiana Reis (UEMA) Dra. Teresinha Queiroz (UFPI) Dra. Zulene Muniz Barbosa (UEMA)